Comparison between Jigsaw and Snowball Method of Active Learning among First Year Medical Undergraduates: An Interventional Study (International Journal of Physiology, 2020)
Present study focuses on comparison between the efficacies of jigsaw and snowball methods active learning.An interventional study was conducted among first year medical undergraduates. Overall, 167 studentsstudied by jigsaw method and 173 students studied by Snowball method. To study the preferences of studentsbetween Jigsaw and Snowball metSelf-directed learning, Jigsaw method, Snowball method, Physiology.hod a structured questionnaire using five point likert scale was used. Boththe method significantly improved the knowledge of students. Overall response based on the questionnaireabout jigsaw method was positive. Students found it to be simple, enjoyable and effective means of learning.